1991
DOI: 10.3354/meps073263
|View full text |Cite
|
Sign up to set email alerts
|

Decimeter scale heterogeneity in the plankton during a pycnocline bloom of Gyrodinium aureolum

Abstract: ABSTRACT-Vertical heterogeneity of pelagic organisms in a subsurface bloom of Gyrodinium aureolum (Hulburt) was studied on the decimeter scale by a high resolution sampler In the Kattegat, Denmark, durlng August 1990. Maximum concentrations of 3.25 X 106 G. aureolum I -' and 72 pg chlorophyll a I-' were recorded in the pycnocline at a depth of 14 m with 5 "10 of surface irrad~ance. Dinoflagellates were confined to a 1 m thick layer which contained more chlorophyll than the rest of the water column In situ prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(67 citation statements)
references
References 11 publications
4
62
1
Order By: Relevance
“…Blooms in stratified water columns remain confined mainly within the pycnocline layers (Birrien et al 1991). Bjoernsen & Nielsen (1991) studied the distribution of G. aureolum in a pycnocline layer in the Kattegat with a high-resolution sampler. They observed a strong heterogeneity of the dinoflagellate population in the decimetre scale and concluded that G. aureolum at that time formed a more or less coherent 'magic carpet' in the pycnocline layer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Blooms in stratified water columns remain confined mainly within the pycnocline layers (Birrien et al 1991). Bjoernsen & Nielsen (1991) studied the distribution of G. aureolum in a pycnocline layer in the Kattegat with a high-resolution sampler. They observed a strong heterogeneity of the dinoflagellate population in the decimetre scale and concluded that G. aureolum at that time formed a more or less coherent 'magic carpet' in the pycnocline layer.…”
Section: Resultsmentioning
confidence: 99%
“…When stratification is greater, the population exhibits a non-migrating maximum in the pycnocline layer (Bjoernsen & Nielsen 1991;Arzul et al 1993), relying mainly on nitrogen remineralization (Le Corre et al 1993). It is not possible to estimate from the available data the lowest density gradient through which migration still persists.…”
Section: Introductionmentioning
confidence: 99%
“…While thin layers can contain mixed species assemblages and trophic levels , phytoplankton thin layers are often dominated by high concentrations of a single species (e.g. Nishitani et al, 1985;Richardson and Kullenberg, 1987;Nielsen et al, 1990;Dahl and Tangen, 1993;Bjørnsen and Nielsen, 1991;Carpenter et al, 1995;Gentien et al, 1995;Gisselson et al, 2002;Rines et al, 2002;Sullivan et al, 2003Sullivan et al, , 2005VeloSuarez et al, 2008). Interestingly, a large number of harmful algal species have been observed in thin layers (Rines et al, 2002, this issue;Sullivan et al, 2003Sullivan et al, , 2005McManus et al, 2008), indicating that understanding thin layers could be critical to harmful algal bloom research.…”
Section: Ecological Importancementioning
confidence: 99%
“…First, far from being unusual or rare, it is now clear that thin layers of plankton are common features and can be found in a wide variety of environments (Derenbach et al, � 1979;Bjørnsen and Nielsen, 1991;Donaghay et al, 1992;Cowles and Desiderio, 1993;Carpenter et al, 1995;Holliday et al, 1998;Dekshenieks et al, 2001;McManus et al, 2003;Ryan et al, 2008). As thin plankton layers can often contain 50-75% (or more) of the total biomass in the water column (Holliday et al, 1998;Cowles et al, 1998;Sullivan et al, this issue), thin layers are likely to be concentrated areas of intense biological activity, likely playing a critical role in the life histories and evolutionary trajectories of many species that are found in or interact with thin layers.…”
Section: Ecological Importancementioning
confidence: 99%
“…Uneven plankton distributions have subsequently been widely described, e.g. [39][40][41][42][43][44]. However, intermittency has seldom been quantified, despite the increasing evidence of the intermittent nature Figure 2: Illustration of Lagrangian and Eulerian perceptions of the environment by marine organisms.…”
Section: Intermittency In Marine Sciencesmentioning
confidence: 99%